Silicon carbide substrate with regular crystalline phase structure

By dividing areas in the silicon carbide substrate and using composite coating technology, the lattice distortion problem caused by defects during the growth of the silicon carbide substrate is solved, and the regularity and performance of the substrate are improved, which is suitable for efficient mass production.

CN119320992APending Publication Date: 2025-01-17SICC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310869277.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

During the growth process, silicon carbide single crystal substrates are subject to defects such as polycrystalline, polytype, microtube, dislocation, etc. due to Si/C ratio imbalance, impurity introduction, and temperature ladder changes, resulting in lattice distortion, affecting performance and yield.

Method used

By dividing the silicon carbide substrate into a first square region containing microtubes or dislocations and a second square region containing no microtubes or dislocations, the proportion of the second square region is greater than the first square region, thereby reducing lattice distortion and Defect density, composite coating is used to coat the graphite crucible to improve environmental stability and crystal quality.

Benefits of technology

It improves the lattice structure regularity of the silicon carbide substrate, reduces defect density, improves device performance and yield, is suitable for large-scale production, and saves processing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320992A_ABST
    Figure CN119320992A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon carbide substrate with a regular crystal phase structure, and belongs to the technical field of silicon carbide production and processing. The silicon carbide substrate is divided into first square regions which contain microtubes or dislocations and are 100 [mu] m long and second square regions which do not contain microtubes or dislocations and are 100 [mu] m long, and the ratio of the number of the first square regions to the number of the second square regions is 1: (1.64-21.4); the in-vivo stress of the first square region is greater than the in-vivo stress of the second square region. The silicon carbide substrate is high in lattice structure regularity, so that lattice distortion and defect density are reduced, the performance and yield of the silicon carbide substrate can be improved, and the application range of the silicon carbide substrate is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a silicon carbide substrate with a regular crystal structure, and belongs to the technical field of silicon carbide production and processing. Background Art

[0002] Silicon carbide single crystal substrates have become the preferred semiconductor material for the preparation of GaN-based high-frequency microwave devices due to their excellent physical properties such as large bandgap, high resistivity and thermal conductivity, and strong breakdown field. With the continuous development of 5G technology, the market demand for silicon carbide single crystal substrates continues to expand. More importantly, mass commercial applications have also put forward higher requirements on the quality of silicon carbide single crystal substrates.

[0003] Silicon carbide substrates are processed from silicon carbide crystals. During the growth process of silicon carbide crystals, due to the imbalance of Si / C ratio, the introduction of impurities and temperature gradient changes, various defects such as polycrystalline, polymorphic, micropipes, dislocations, etc. are easily introduced into the crystals. Defects will cause lattice distortion, and more seriously, the crystal form will change, such as the generation of 4H, 6H, 3C, 15R and other polymorphic symbiosis. Lattice distortion releases stress by generating defects, that is, introducing internal stress into silicon carbide. The existence of the above defects will have a great impact on the performance of silicon carbide crystals and silicon carbide substrates, and the yield rate during mass production. Therefore, improving the quality of crystals and reducing crystal defects have always been the research focus of silicon carbide devices. Summary of the invention

[0004] In order to solve the above problems, a silicon carbide substrate with a regular crystal phase structure is provided, wherein the silicon carbide substrate is divided into a first square region containing micropipes or dislocations and a second square region not containing micropipes or dislocations, and the proportion of the second square region is greater than that of the first square region, which proves that the lattice structure of the silicon carbide substrate itself is highly regular, thereby reducing lattice distortion and defect density, being able to improve the performance and yield of the silicon carbide substrate, and expanding the scope of use of the silicon carbide substrate.

[0005] According to one aspect of the present application, a silicon carbide substrate with a regular crystal structure is provided, the silicon carbide substrate comprising a first main surface and a second main surface opposite to the first main surface;

[0006] Dividing the silicon carbide substrate into a first square region containing micropipes or dislocations and having a length of 100 μm, and a second square region not containing micropipes or dislocations and having a length of 100 μm, wherein the ratio of the number of the first square regions to the number of the second square regions is 1:(12.9-21.4);

[0007] The internal stress of the first square region is greater than the internal stress of the second square region. The internal stress is a stress value detected at a region vertically extending from the first main surface and / or the second main surface into the silicon carbide substrate by 30%-60% of the substrate thickness.

[0008] The smaller the ratio of the number of the first square regions to the number of the second square regions, the larger the proportion of the second square regions, the lower the defect density of the silicon carbide substrate, and the better the quality of the silicon carbide substrate. Preferably, the ratio of the number of the first square regions to the number of the second square regions is 1:(19.7-21.4).

[0009] Due to the limitation of the shape of the silicon carbide substrate, for the first square region and the second square region at the edge of the silicon carbide substrate, there may be a situation where the area of ​​one first square region or the second square region is not satisfied, so the number of the first square region and the second square region may not be an integer. For example, the edge of the silicon carbide substrate can only be divided into a 50μm region, but the region does not contain dislocations or micropipes, then it is calculated as 0.25 second square regions according to the area ratio.

[0010] Optionally, at any plane parallel to the first main surface and / or the second main surface, the radial internal stress of the first square area is -20 to 40 MPa, preferably -19.6 to 39.3 MPa, and the radial internal stress of the second square area is -10 to 20 MPa, preferably 9.6 to 19.1 MPa; and / or

[0011] The silicon carbide substrate has a diameter of 150 mm or more, preferably 200 mm or more.

[0012] Since the tensile and compressive stresses inside the silicon carbide substrate cause the interplanar spacing d to expand and contract accordingly, when using Raman to test stress, the Raman peak intensity will move to low frequency or high frequency. When the substrate is subjected to tensile stress, the Raman peak shifts to low frequency, and the obtained stress value is positive. When the substrate is subjected to compressive stress, the Raman peak shifts to high frequency, and the obtained stress value is negative. Therefore, the positive and negative before the stress value in this application represent the force direction inside the substrate, and the absolute value of the value represents the magnitude of the stress. For example, when the radial stress in the first square area is -20MPa and the radial internal stress in the second square area is -10MPa, it means that the radial internal stress in the first square area and the second square area are both compressive stresses, and the radial internal pressure in the first square area is greater than the radial internal pressure in the second square area.

[0013] According to the stress values ​​of the first square region and the second square region, the introduction of micropipes or dislocations increases the stress in the first square region, proving that micropipes or dislocations can change the crystal plane spacing of the substrate. If the stresses of the first square region and the second square region are closer, it proves that the number of micropipes or dislocations in the first square region is smaller.

[0014] Optionally, in the first square region, the number of microtubes is less than 4, preferably 1, more preferably 0; or

[0015] In the first square region, the number of dislocations is less than 14, preferably 10, more preferably 5, and more preferably 0.

[0016] Optionally, the second square region is free of polymorphic defects, polycrystalline defects, and void defects.

[0017] Optionally, at any plane parallel to the first main surface and / or the second main surface, S1 represents the average absolute value of the radial internal stress in all the first square regions, and S2 represents the average absolute value of the radial internal stress in any of the first square regions, and 0.2≤S1 / S2≤1.7.

[0018] Optionally, at any plane parallel to the first main surface and / or the second main surface, S3 represents the average absolute value of the radial internal stress in all the second square regions, and S4 represents the average absolute value of the radial internal stress in any second square region, and 0.3≤S3 / S4≤1.2.

[0019] Preferably, 1.4≤S1 / S3≤5.1.

[0020] The silicon carbide substrate is subjected to multi-point stress detection. The above-mentioned average absolute value refers to the value obtained by dividing the sum of the absolute values ​​of stress at all detection points in the area by the number of detection points. The multi-point detection can be performed by selecting multiple points at different positions in the area for detection, or by performing a mapping test on the substrate.

[0021] The above ratio of S1 / S2 represents the difference between any first square region and the average value of all first square regions in the radial direction. The closer this ratio is to 1, the smaller the difference between the radial internal stress of all first square regions is, and the more uniform the defect distribution on the silicon carbide substrate is. Similarly, the above ratio of S3 / S4 represents the difference between any second square region and the average value of all second square regions in the radial direction. The closer this ratio is to 1, the smaller the difference between the radial internal stress of all second square regions is, and the more uniform the stress distribution of the silicon carbide substrate is. The ratio of S1 / S3 represents the average radial internal stress ratio of the defective region and the defect-free region of the silicon carbide substrate in the radial direction, and represents the difference between all first square regions and second square regions. The more defects there are in the first square region, the greater the stress value of the first square region is. Therefore, the smaller the ratio of S1 / S3 is, the fewer defects there are on the silicon carbide substrate.

[0022] Optionally, at any plane parallel to the first major surface and / or the second major surface, S max1 S is the maximum radial internal stress in any of the first square regions, min1 Denote as the minimum value of radial internal stress in any first square region, △S1 = S max1 -S min1 , 10MPa≤△S1≤40MPa, S max2 S is the maximum radial internal stress in any second square region. min2 Denote as the minimum value of radial internal stress in any second square region, △S2 = S max2 -S min2 , 2MPa≤△S2≤20MPa;

[0023] Preferably, 10.1 MPa≤△S1≤39.5 MPa, 2.8 MPa≤△S2≤19.2 MPa.

[0024] More preferably, 10.1 MPa≤△S1≤27.2 MPa, 2.8 MPa≤△S2≤12.2 MPa.

[0025] The above-mentioned maximum radial internal stress and minimum radial internal stress mean the true value of the radial internal stress, which distinguishes between compressive stress and tensile stress in the radial direction. For example, at any plane parallel to the first main surface and / or the second main surface, the radial internal stress of the first square area is -10~5MPa, then the maximum radial internal stress is 5MPa, and the minimum radial internal stress is -10MPa, and △S1 is 15MPa. △S1 and △S2 respectively represent the degree of change in the radial interplanar spacing between the first square area and the second square area. The smaller the above △S1 and △S2 are, the smaller the radial interplanar spacing change of the silicon carbide substrate is.

[0026] Optionally, an axial test is performed extending vertically into the silicon carbide substrate from any point on the first main surface and / or the second main surface, and the axial internal stress of the first square region is -10 to 30 MPa, preferably -9.6 to 29.2 MPa, and the axial internal stress of the second square region is -5 to 10 MPa, preferably -4.7 to 9.9 MPa.

[0027] Optionally, an axial test is performed extending vertically into the silicon carbide substrate from any point on the first main surface and / or the second main surface, S5 represents the average absolute value of the axial internal stress in all the first square regions, S6 represents the average absolute value of the axial internal stress in any of the first square regions, and 0.6≤S5 / S6≤1.7.

[0028] Optionally, an axial test is performed by extending vertically into the silicon carbide substrate from any point of the first main surface and / or the second main surface, S7 represents the average absolute value of the axial internal stress in all the second square regions, S8 represents the average absolute value of the axial internal stress in any second square region, and 0.7≤S7 / S8≤1.2;

[0029] Preferably, 1.6≤S5 / S7≤4.2.

[0030] The above ratio of S5 / S6 represents the difference between any first square region and the average value of all first square regions in the axial direction. The closer this ratio is to 1, the smaller the difference between the axial internal stresses of all first square regions is, and the more uniform the defect distribution on the silicon carbide substrate is. Similarly, the above ratio of S7 / S8 represents the difference between any second square region and the average value of all second square regions in the axial direction. The closer this ratio is to 1, the smaller the difference between the axial internal stresses of all second square regions is, and the more uniform the stress distribution of the silicon carbide substrate is. The ratio of S5 / S7 represents the average axial internal stress ratio of the defective region and the defect-free region of the silicon carbide substrate in the axial direction, and represents the difference between all first square regions and second square regions. The more defects there are in the first square region, the greater the stress value of the first square region is. Therefore, the smaller the ratio of S5 / S7 is, the fewer defects there are on the silicon carbide substrate.

[0031] Optionally, an axial test is performed by extending vertically from any point of the first main surface and / or the second main surface into the silicon carbide substrate, S max3 S is the maximum axial internal stress in any of the first square regions, min3 Denote as the minimum axial internal stress in any of the first square regions, 4.7MPa≤△S3≤20.4MPa, S max4 S is the maximum axial internal stress in any second square region. min4 Denote as the minimum axial internal stress in any of the first square regions, △S4 = S max4 -S min4 ,1.2MPa≤△S4≤14.1MPa.

[0032] Preferably, 4.7MPa≤△S3≤13.5MPa, 1.2MPa≤△S4≤8.4MPa.

[0033] The above-mentioned maximum axial internal stress and minimum axial internal stress mean the true value of the axial internal stress. Compressive stress and tensile stress are distinguished in the axial direction. An axial test is performed vertically extending into the silicon carbide substrate from any point of the first main surface and / or the second main surface. The axial internal stress in the first square area is -10 to 5 MPa, then the maximum value of the axial internal stress is 5 MPa, the minimum value of the axial internal stress is -10 MPa, and △S3 is 15 MPa. △S3 and △S4 respectively represent the degree of change in the axial interplanar spacing between the first square area and the second square area. The smaller the above △S3 and △S4 are, the smaller the change in the axial interplanar spacing of the silicon carbide substrate is.

[0034] The stress values ​​of this application include absolute stress and relative stress. Absolute stress can reflect the difference between the substrate and a perfect SiC crystal without defects, and is used to determine the stress level of the SiC substrate. However, since it is difficult to achieve a perfect SiC substrate with current technology, the relative stress distribution within the substrate surface can be determined by relative stress.

[0035] For example, when the absolute stress of the substrate is large and the relative stress is small, it means that there are more in-plane defects, but the stress distribution is uniform, the crystal quality is poor, and the uniformity quality in each area of ​​the substrate is poor; if the absolute stress is small and the relative stress is large, the overall substrate quality is good, but there are abnormal quality deviations in some areas.

[0036] The reference value of absolute stress in this application is the reference stress calculated based on the standard Raman peak position obtained based on the perfect lattice parameters of SiC, which is marked as 0; the relative stress is to take a reference value on the entire test plane, and the value of each test point is related to the reference value for numerical calculation to obtain the relative stress value of the test point. The reference value includes but is not limited to any one of the median, mean, mode or other statistical function calculation results of all stress values ​​on the entire test plane.

[0037] Optionally, the crystal form of the silicon carbide substrate is one of 2H-SiC, 4H-SiC, 6H-SiC, 3C-SiC, and 15R-SiC, preferably 4H-SiC.

[0038] Optionally, the curvature of the silicon carbide substrate is -100 μm to 100 μm, -50 μm to 50 μm, preferably -20 μm to 20 μm, and more preferably -10 μm to 10 μm.

[0039] Optionally, the silicon carbide substrate is a semi-insulating silicon carbide substrate or a conductive silicon carbide substrate.

[0040] Optionally, the local thickness deviation of the first square region is 0.1-1 μm, and the local thickness deviation of the second square region is 0.1-1 μm.

[0041] The silicon carbide substrate described in any of the above items is made by processing a silicon carbide single crystal. According to another aspect of the present application, a method for preparing a silicon carbide single crystal is provided, comprising the following steps:

[0042] (1) Adding silicon carbide powder into a graphite crucible;

[0043] (2) Evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300-500mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 Below mbar;

[0044] (3) introducing high-purity inert gas into the furnace body, raising the pressure to 10-100 mbar within 1-3 hours, and continuously introducing high-purity inert gas and maintaining the pressure constant;

[0045] (4) Crystal growth stage: While maintaining the pressure unchanged, the temperature inside the furnace is raised to the single crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;

[0046] (5) After the single crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the silicon carbide single crystal.

[0047] Optionally, the graphite crucible is coated with a composite coating, and the composite coating comprises:

[0048] Ta x C y The permeation layer, the Ta x C y The infiltration layer is deposited on a graphite substrate, wherein 0 <x<1,0<y<1;

[0049] TaC coating, the TaC coating is coated on the Ta x C y On the penetration layer.

[0050] The Ta x C y The permeation layer is formed on the surface and inside of the graphite substrate. x C y The infiltration layer is evenly distributed on the surface of the graphite substrate and has good compactness, which improves the environmental stability of the silicon carbide crystal during the growth process and reduces the thermal expansion of the graphite substrate.

[0051] Optionally, the Ta x C y Ta in the permeate layer x C y The grains grow anisotropically, and the TaC grains in the TaC coating grow along the

[200] and

[220] directions; x C y Ta in the permeate layer x C y The TaC grains and the TaC grains in the TaC coating are arranged in an alternating manner. x C y Ta in the permeate layer x C y The grains are arranged in a staggered manner. x C yThe size of the grains is 5-30 μm; the TaC grains in the TaC coating are arranged in a stacking staggered manner, and the size of the TaC grains is 15-40 μm.

[0052] Ta x C y The grain size can reduce the Ta x C y Stress in the penetration layer, avoid Ta x C y The formation of the infiltration layer forms a clear grain boundary and avoids Ta x C y The generation of cracks in the permeation layer prevents the graphite substrate from squeezing the crystal.

[0053] The TaC grains in the TaC coating grow in an oriented manner along the

[200] and

[220] directions, which can improve the compactness of the TaC coating, thereby improving the bonding strength between the composite coating and the graphite substrate, as well as the temperature resistance and thermal chemical corrosion resistance of the composite coating, thereby reducing the interference of the graphite substrate in the crystal growth process, which is conducive to the preparation of silicon carbide crystals with uniform quality.

[0054] Optionally, the Ta x C y The thickness of the permeation layer is 10-450 μm, the thickness of the TaC coating is 30-400 μm, and the Ta x C y The total thickness of the permeation layer and the TaC coating is 40-500 μm.

[0055] The beneficial effects of this application include but are not limited to:

[0056] 1. According to the silicon carbide substrate of the present application, the lattice structure itself has high regularity, thereby reducing the lattice distortion and defect density. Using it to prepare silicon carbide devices can improve the performance and yield of silicon carbide devices, facilitate mass production and processing, and save the processing cost of silicon carbide devices.

[0057] 2. The axial internal stress of the silicon carbide substrate of the present application is smaller than the radial internal stress, which proves that the silicon carbide substrate has small axial difference and uniform axial internal stress distribution. It can be regarded as a body with uniform stress distribution and can be used as an epitaxial substrate or seed crystal, which is beneficial to improve the production quality of downstream products.

[0058] 3. According to the silicon carbide substrate of the present application, through the ratio of the internal stress of any first square area to all the first square areas and the ratio of the internal stress of any second square area to all the second square areas, it can be known that the differences between the first square area and the second square area in the radial and axial directions are small, respectively, and according to the ratio of the internal stress of all the first square areas to all the second square areas, it can be known that the defects in the first square area account for a small proportion, thereby proving that the quality of the silicon carbide substrate is good.

[0059] 4. The present application utilizes a composite coating formed on the surface of the crucible to improve the tolerance of the graphite crucible and reduce the impact of the graphite crucible on the crystal growth process, thereby improving the stability of the crystal environment and the uniformity of the temperature field, reducing the number of defects and impurity content in the crystal, thereby preparing a silicon carbide substrate with a low defect density.

[0060] 5. According to the quantitative testing method of the present application, the detected stress also includes the stress in the substrate caused by lattice distortion that has not yet been released through defects. Therefore, according to the stress distribution in various regions of the silicon carbide substrate, the parameters of each process in the crystal growth can be adjusted to prepare a high-quality and low-defect silicon carbide substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0062] Figure 1 Schematic diagram of the in-vivo stress of the Raman equidistant focusing test substrate involved in Example 4 of the present application and the in-vivo stress test results.

[0063] Figure 2 Schematic diagram of the internal stress of the substrate tested by Raman isotropic focusing plane and the internal stress test results involved in Example 4 of the present application.

[0064] Figure 3 Ta involved in crucible 1# of this application x C y EDS Mapping characterization of the permeation layer. DETAILED DESCRIPTION

[0065] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0066] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0067] The principle of using Raman to test the stress of the substrate in the following embodiments is as follows: the Raman spectrometer passes a monochromatic laser of a certain wavelength through a series of optical paths and then converges the laser through an objective lens to irradiate the substrate surface, and the laser photons interact with the substrate lattice to cause photon scattering. The occurrence of Raman scattering is related to the lattice vibration of the substrate itself. When there is residual stress in the sample, the tensile and compressive stresses will cause the atomic bond length to be elongated or shortened accordingly, thereby causing the atomic vibration frequency to decrease or increase, which is reflected in the Raman spectrum as the characteristic peak of the substrate moves to a low frequency or a high frequency, that is, a peak position offset occurs.

[0068] Example 1 Quantitative Testing Method for Substrate Stress

[0069] (1) Calculation of peak position shift and stress conversion coefficient

[0070] First, a single crystal XRD diffractometer is used to test the silicon carbide substrate and the substrate is analyzed according to the reciprocal lattice space. The parameters of the standard 4H-silicon carbide substrate are calculated and compared with the standard parameters. Then, according to the Bragg diffraction equation: 2dsinθ=nλ, where d is the crystal plane spacing, θ is the diffraction half angle, n is the diffraction order, and λ is the wavelength, the θ and d of different substrates are tested. It can be seen that the tensile and compressive stress inside the crystal causes the crystal plane spacing d to expand and contract accordingly. According to the different crystal plane spacings d0 and d x , d x It is divided into d1 and d2, where d0 is the theoretical crystal plane spacing, d1 is the crystal plane spacing after tensile stress, and d1 is greater than d0, and d2 is the crystal plane spacing after compressive stress, and d2 is less than d0. The difference in crystal plane spacing △d at different positions is calculated, △d=d1-d0 or △d=d0-d2.

[0071] The actual peak position of the substrate is obtained according to the Raman test, and the peak position offset △v at different test points is calculated compared with the standard peak position; the stress value σ of the silicon carbide substrate at different test points is calculated in combination with Hooke's law or stress-strain formula, and the ratio of the peak position offset to the stress value at different test points is the peak position offset and the stress conversion coefficient μ, which ranges from -125 to -2500.

[0072] The calculation formula of Hooke's law is σ / S=E×(△d / d0), where S is the area where σ acts, which is a fixed value. When Hooke's law is applicable to microscopic calculations, S is the microscopic area, which can be calculated as unit 1. E is the Young's modulus of the substrate, which is a fixed parameter of the substrate. △d is the difference in crystal plane spacing at different positions, d0 is the theoretical crystal plane spacing, and σ is the stress value that needs to be calculated.

[0073] The calculation formula of stress and strain is σ=E×△d, where E is the Young's modulus of the substrate, which is a fixed parameter of the substrate, △d is the difference in crystal plane spacing at different positions, and σ is the stress value to be calculated.

[0074] (2) Quantitative test method of substrate stress

[0075] First, set the Raman test points. You can perform single-point testing or Mapping scanning of the entire substrate. Therefore, single-point testing is a sporadic coordinate point setting, and Mapping scanning is 10x10~50x50 and more points. You can choose the appropriate test method according to the properties of the substrate to determine the Raman test coordinate diagram of the silicon carbide substrate.

[0076] The test results are then output, including but not limited to editable peak position, peak intensity data and Mapping.

[0077] The output data is then subjected to peak position fitting, where fitting functions include but are not limited to Gaussian, Lorentz, GaussLor, AGauss, Aloren and AGaussLor, to obtain precise peak position values ​​and peak position offsets, with the peak position accurate to more than one decimal place.

[0078] Finally, according to the peak shift and stress conversion coefficient μ calculated in (1) and the peak shift △v obtained in the Raman test, the stress value of silicon carbide is calculated as follows: σ(MPa)=μ×△v(cm -1 ), and finally obtain the stress test image of the substrate.

[0079] Example 2: Test of curvature of substrate surface

[0080] Since SiC is subjected to a lot of external mechanical stress during the process of preparing wafers from crystals through a series of processes, it is difficult to ensure that the surface is completely level, that is, there is a certain degree of curvature. In order to eliminate the influence of substrate surface curvature on substrate surface stress and internal stress test, it is necessary to first perform a curvature test on the substrate. According to the curvature, the substrate surface stress is tested with equal spacing focus, and the substrate internal stress is tested with equal spacing focus or equal focus plane.

[0081] After the curvature test, the tester needs to be calibrated using single crystal silicon. First, a Z-axis mapping test is performed on the single crystal Si to confirm that it is a Gaussian distribution. The surface of the single crystal Si substrate is taken as the zero point, and an axial mapping test is performed from -100μm inside the single crystal Si substrate to +20μm above the single crystal Si substrate to analyze the change in Raman signal intensity. The single crystal Si substrate is a non-transparent material, so its peak intensity presents a Gaussian distribution, with the surface zero point position as the symmetry axis; then a surface focusing single point test is performed on the single crystal Si, and the single crystal Si Raman peak position is made to be 520.70cm through the correction instrument. -1 , at this time, it means that the instrument optical path has been calibrated.

[0082] The 4H-SiC substrate was tested in the Z direction using a calibrated tester. The Raman laser was emitted from -100μm inside the 4H-SiC substrate to +20μm above the 4H-SiC substrate. The 4H-SiC substrate and other silicon carbides are transparent materials, so the Raman laser can penetrate into the silicon carbide substrate, and the feedback signal gradually weakens as the Raman laser incident depth increases. Other silicon carbides include semi-insulating, conductive, and 3C, 4H, 15R, 6H and other silicon carbide substrates with different crystal forms. Therefore, the Raman peak intensity of the silicon carbide substrate gradually decreases as the Raman laser penetrates deeper into the silicon carbide substrate.

[0083] The Raman device's autofocus function can be used to automatically find the strongest peak of the test signal on the substrate surface, so that the curvature of the substrate surface can be measured with the help of this function. The specific method is as follows:

[0084] S1: First, ensure that the test platform is level, select a fixed origin (0,0) on the test platform, and mark the point as the three-dimensional coordinate (0,0,0);

[0085] S2: Raise the objective lens to a height that does not touch the substrate according to the thickness of the substrate, and automatically focus on any point on the substrate surface where the test signal is the strongest. Mark this position as (a, b, c), then adjust the Raman laser downward by a distance of H and focus on the position to (a, b, cH);

[0086] S3: Adjust the Raman laser test position to (0,0,cH) to perform an iso-focal plane test to obtain a two-dimensional peak intensity scan of the substrate surface. According to the peak intensity distribution relationship of the silicon carbide substrate and the two-dimensional peak intensity scan, the distance between the focal plane of the Raman laser and the surface of the silicon carbide substrate can be obtained, thereby obtaining the in-plane curvature of the substrate and obtaining the in-plane curvature distribution map of the substrate.

[0087] Example 3 Axial test to distinguish substrate surface stress from internal stress

[0088] Since the substrate is affected by the temperature field and the introduction of inclusions during the crystal growth process, thermal stress and residual stress exist inside the crystal, and the crystal is obtained after a series of cutting, grinding and polishing. The processing process of the crystal to form the substrate will cause surface lattice distortion, thereby generating surface stress. In order to further distinguish the surface stress from the body stress of the substrate, the substrate is subjected to axial testing according to the light transmittance characteristics of silicon carbide, namely, Z-direction Mapping, with the substrate surface as the zero point. The test range of the axial test is from -150μm to -30μm inside the substrate to above the substrate surface.

[0089] During the test, the laser spot gradually focuses upward from the substrate body to the damaged stress extension layer, further to the surface damaged layer, and then continues to focus upward into the air to determine the thickness of the substrate surface damaged layer and the damaged stress extension layer. With the substrate surface as the zero point, the test range of the axial test is that the Raman laser spot gradually moves upward from -100μm inside the substrate to 30μm above the substrate surface. Five points of the substrate are tested up and down, left and right. The five points on the substrate show the same trend, and there is only a difference in the maximum negative stress at the surface damage.

[0090] The laser moves from -100μm inside the substrate to -30μm, at which time the stress fluctuates up and down along the horizontal line, indicating that the internal stress is uniform; when the laser spot is focused on the damaged stress extension layer, the stress curve begins to show a downward trend at -30μm, and the downward trend of stress gradually increases. When it approaches the zero point on the substrate surface, it reaches the maximum negative stress value, which is the stress value of the surface damaged layer; finally, the laser spot continues to move upward and gradually leaves the substrate surface into the air, and the stress shows a rapid rise to chaotic fluctuations. Therefore, the thickness of the surface damaged layer and the damaged stress extension layer of the substrate can be determined according to the axial test results of the substrate, thereby distinguishing the stress in the substrate into surface stress and internal stress, which provides a theoretical basis for the subsequent quantitative testing of surface stress and internal stress in the substrate.

[0091] Example 4 Quantitative Testing of Stress in the Substrate

[0092] During the PVT crystal growth process, silicon carbide is affected by temperature gradient changes and the intrusion of inclusions, resulting in residual stress in the crystal. Different from the surface processing stress, the internal stress is located at a certain depth from the surface, reflecting the thermal stress and residual stress of crystal growth. In addition, silicon carbide undergoes a large amount of external mechanical stress in the process of preparing the substrate from the crystal through a series of processing, and it is difficult to ensure that the surface is completely horizontal, that is, there is a certain degree of curvature on the surface of the substrate. According to the measurement method of the curvature of the substrate surface obtained by Raman testing in Example 2, this embodiment, combined with the physical properties of silicon carbide, involves a method for quantitatively characterizing its internal stress that is not affected by surface curvature.

[0093] According to the physical property of silicon carbide being light-transmissive, the method of using Raman to quantitatively characterize the internal stress of the substrate is divided into equal-spacing focusing test and equal-focusing plane test, as follows:

[0094] 1. Equal spacing focus test

[0095] The principle of equidistant focusing test is as follows Figure 1 As shown in (a), under this test mode, the focal depth (d) of the Raman laser focused on the inside of the substrate at different test points remains unchanged. First, the penetration depth (Dp) of the Raman laser is calculated according to the following formula:

[0096]

[0097] In the above formula, Dp is the penetration depth of Raman excitation in the sample, α is the absorption coefficient, λ is the laser wavelength, and k is the extinction coefficient. The specific value of the penetration depth (Dp) is calculated according to the above formula, and a suitable focusing depth (d) is selected. The requirement that needs to be met is that the penetration depth (Dp) is greater than the focusing depth (d), and since the test is for internal stress, the focusing depth d needs to be greater than the thickness of the surface damage layer and the damage stress extension layer tested in Example 3.

[0098] The Raman laser spot diameter (D) is then calculated according to the following formula:

[0099] Where λ is the laser wavelength and Na is the numerical aperture of the device.

[0100] The spot diameter (D) is the short axis diameter of the laser spot. The larger the value, the stronger the peak intensity of Raman at each test position, and the more impurity peaks there are, which affects the detection accuracy of Raman. When λ is determined, if the value of Na is large, the peak intensity is very weak, which will also affect the Raman detection accuracy. Therefore, it is necessary to select appropriate λ and Na to improve the accuracy of the test method.

[0101] According to the characteristics of silicon carbide materials, the peak intensity reaches the highest when the laser is focused on the substrate surface. Therefore, the automatic focusing function of the Raman tester can be used to focus the laser on the substrate surface. Then, according to the focus depth (d) determined above, the equidistant focusing test is performed on different positions of the substrate, that is, the distance between the focus plane and the substrate surface is always equal. This method is not affected by the bending and warping of the substrate surface, so that the obtained Raman peak intensity is always maintained at the axial maximum value at the test point. According to the stress quantitative test method of Example 1, the in vivo stress test result of the substrate is obtained. Figure 1 (b) as shown.

[0102] 2. Equifocal plane test

[0103] The principle of isofocal plane test is as follows Figure 2 As shown in (a), under this test mode, the focus depth (d) of the Raman laser spot focused on the inside of the substrate changes at different test points. The laser spot at different test points is focused on the same plane inside the substrate. The penetration depth (Dp) of the Raman laser is calculated according to the same formula as the equidistant focusing test, and the appropriate focus depth (d) is selected in the same selection method.

[0104] Since the focus planes in this test method are equal, combined with the characteristics of silicon carbide, when the laser is focused on the substrate surface, the peak intensity reaches the highest and the signal gradually decays with the increase of the focus depth. And according to the effective signal-to-noise ratio tested by the Raman tester, it is found that the effective signal-to-noise ratio is inversely correlated with the Raman laser focus depth (d). Therefore, in this test method, the focus depth (d) at different test points needs to be combined with the curvature of the substrate to obtain the effective peak position offset through the stress quantitative test method of Example 1, thereby reducing the error of the in vivo stress test. The in vivo stress test results of the substrate obtained by this test method are as follows: Figure 2 (b) as shown.

[0105] Through the above two testing methods of equal spacing focusing and equal focusing plane, the peak position offset inside the substrate is obtained, and the internal stress distribution of the substrate is calculated. The difference between the internal stress values ​​of the substrate calculated by the equal spacing focusing test and the equal focusing plane test is ≤0.2MPa, and the peak position difference between the equal spacing focusing test and the equal focusing plane test is <0.0005cm -1 The above two methods can verify the accuracy of the quantitative detection method of the present application, and the accuracy of the test method can be further improved according to the setting of the focus depth and the spot diameter.

[0106] The internal stress includes the internal absolute stress and the internal relative stress, which is illustrated by taking 4H-SiC as an example:

[0107] The absolute stress in the body is calculated by subtracting the measured 4H-SiC peak position from the standard peak position to determine the simplified wave vector peak position, such as FTO (2 / 4). The absolute stress in the body is calculated as:

[0108] σabsolute=μ×(v 实际 -V FTO(2 / 4) ), σ is in MPa, v 实际 and V FTO(2 / 4) The unit is cm -1 , where v 实际 is the actual FTO(2 / 4) peak position at the substrate test point, V FTO(2 / 4) It is the standard peak position of FTO (2 / 4) of the substrate;

[0109] The relative stress in the body is calculated by subtracting the measured values ​​of the same simplified wave vector peak position at any two points in the SiC substrate surface, such as the FTO (2 / 4) peak position. The calculation formula for the relative stress in the body is:

[0110] σrelative=μ×(v (x1,y1) -V (x2,y2) ), σ is in MPa, v (x1,y1) and V (x2,y2) The unit is cm -1 , where v (x1,y1)is the actual FTO(2 / 4) peak position at the substrate test point, V (x2,y2) is the actual FTO (2 / 4) peak position of the relative point of the substrate. The relative stress value of the test point is calculated according to the above calculation formula. If the relative value of σ is positive, it means that the stress of the test point relative to the relative point is tensile stress. If the relative value of σ is negative, it means that the stress of the test point relative to the relative point is compressive stress.

[0111] Example 5

[0112] This embodiment relates to a method for preparing a graphite crucible for growing silicon carbide, comprising the following steps:

[0113] 1) Soaking the graphite substrate in a tantalum pentachloride solution, wherein the concentration of tantalum pentachloride is 5%-95%, the porosity of the graphite substrate is 5%-55%, and gas pressure treatment is performed, the gas pressure is 1-2MPa, and the pressurization time is 0.5-1h. The soaked graphite substrate is dried and calcined to obtain a graphite substrate with Ta x C y Graphite substrate of the infiltration layer;

[0114] 2) Prepare a slurry containing TaC, the slurry comprising: 25-40 parts of TaC powder, 20-35 parts of solvent, 15-25 parts of co-solvent, 1-3 parts of defoamer, 2-5 parts of thickener, 5-15 parts of straight-chain saturated aliphatic hydrocarbon, 1-3 parts of carbon powder, and spray the slurry onto the surface with TaC. x C y The surface of the graphite substrate of the infiltration layer is dried and then sintered under an inert gas: sintering at 700-900 mbar and 500-700°C for 3-5 hours; then the pressure is increased to 1000-1100 mbar, the temperature is increased to 1600-1800°C, and sintering is performed for 8-10 hours; finally, the pressure is increased to 145-155 kPa, the temperature is increased to 2200-2400°C, and sintering is performed for 14-16 hours, and finally the temperature is reduced to room temperature and normal pressure within 15-25 hours to obtain the graphite crucible.

[0115] Preferably, the calcination in step 1) is carried out under an inert gas, and the dried graphite substrate is placed in a vacuum furnace for stepwise heating and stepwise cooling:

[0116] Stepwise heating: heating to 250-350℃, calcining for 4-6h, then heating to 850-950℃, calcining for 2.5-3.5h, and finally heating to 1200-1300℃, calcining for 3-5h;

[0117] Step cooling: cool to 900-1100℃, maintain for 0.5-2h, then cool to 750-850℃, maintain for 0.5-1h, and finally cool to room temperature at a cooling rate of 15-25℃ / h.

[0118] Preferably, the pressure in the vacuum furnace during calcination is 800-1000 mbar.

[0119] Crucibles 1#-6# and comparative crucibles D1#-D3# were prepared according to the above preparation method, as follows:

[0120] Crucible 1#

[0121] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.1 MPa / min. When the pressure in the pressure chamber reaches 1 MPa, the pressure is maintained for 1 hour, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace, dried at 60° C. for 7 hours, and then argon gas is introduced into the vacuum furnace to maintain the pressure in the furnace at 900 mbar for calcination. The temperature is raised in a stepwise manner: raised to 300° C. for 1 hour, and calcined for 5 hours; then raised to 900° C. for 2 hours, and calcined for 3 hours; finally raised to 1250° C. for 1 hour, and calcined for 4 hours; and a staged cooling is started: the temperature is lowered to 1000° C. for 1 hour, and maintained for 1 hour, and then the temperature is lowered to 800° C. for 1 hour, and maintained for 1 hour, and finally the temperature is lowered to room temperature at a rate of 20° C. / h to obtain a graphite substrate with Ta x C y Graphite substrate of the infiltration layer.

[0122] 2) 4N grade TaC was dissolved in an organic solvent to prepare a TaC-containing slurry, which included: 32.7 parts of TaC powder, 25 parts of ethanol, 20 parts of tetrahydrofuran, 1.5 parts of BYK defoamer, 3.5 parts of cellulose ether, 10 parts of straight-chain saturated aliphatic hydrocarbon, and 1.3 parts of carbon powder. After mixing and stirring the above components for 2.5 hours, the slurry was sprayed onto the surface of the TaC-containing surface using a sprayer. x C y The surface of the graphite substrate of the infiltration layer is placed in a heating furnace, the temperature is raised to 200°C in an air environment and dried for 10 hours, then argon is introduced into the heating furnace, sintered at 800 mbar and 600°C for 4 hours, then the pressure is raised to 1000 mbar, the temperature is raised to 1700°C, sintered for 9 hours, and finally the pressure is raised to 150 kPa, the temperature is raised to 2300°C, sintered for 15 hours, and finally cooled to room temperature and normal pressure after 20 hours to obtain crucible 1#.

[0123] Crucible 2#

[0124] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.2 MPa / min. When the pressure in the pressure chamber reaches 1 MPa, the pressure is maintained for 1 hour, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace, dried at 80° C. for 5 hours, and then argon gas is introduced into the vacuum furnace to maintain the pressure in the furnace at 800 mbar for calcination. The temperature is raised in a stepwise manner: raised to 250° C. for 1 hour, and calcined for 6 hours; then raised to 850° C. for 2 hours, and calcined for 3.5 hours; finally raised to 1200° C. for 1 hour, and calcined for 5 hours; and a staged cooling is started: the temperature is lowered to 900° C. for 1 hour, and maintained for 2 hours, and then the temperature is lowered to 750° C. for 1 hour, and maintained for 1 hour, and finally the temperature is lowered to room temperature at a rate of 15° C. / h to obtain a graphite substrate with Ta x C y Graphite substrate of the infiltration layer.

[0125] 2) Dissolve 4N grade TaC in an organic solvent to prepare a TaC-containing slurry, which includes: 25 parts of TaC powder, 20 parts of ethanol, 25 parts of tetrahydrofuran, 3 parts of BYK defoamer, 2 parts of cellulose ether, 15 parts of straight-chain saturated aliphatic hydrocarbon, and 3 parts of carbon powder. After mixing and stirring the above components for 2.5 hours, use a sprayer to spray the slurry onto the surface with TaC. x C y The surface of the graphite substrate of the infiltration layer is placed in a heating furnace, the temperature is raised to 180°C in an air environment and dried for 12 hours, then argon is introduced into the heating furnace, sintered at 700 mbar and 700°C for 3 hours, then the pressure is raised to 1000 mbar, the temperature is raised to 1800°C, sintered for 8 hours, and finally the pressure is raised to 145 kPa, the temperature is raised to 2400°C, sintered for 16 hours, and finally cooled to room temperature and normal pressure after 25 hours to obtain crucible 2#.

[0126] Crucible 3#

[0127] 1) placing a tantalum pentachloride n-butanol solution soaked with a graphite substrate in a container, wherein the concentration of tantalum pentachloride in the tantalum pentachloride n-butanol solution is 70%, and the porosity of the graphite substrate is 45%. The container is placed in a pressure chamber for pressurization treatment at a pressurization rate of 0.05 MPa / min. When the pressure in the pressure chamber reaches 2 MPa, the pressure is maintained for 0.5 h, and then the pressure is released. The soaked graphite substrate is transferred to a vacuum furnace and dried at 60°C for 7 h, and then Argon gas was introduced into the vacuum furnace to maintain the pressure at 1000 mbar before calcination. The temperature was raised in a stepwise manner: raised to 350°C for 1 hour and calcined for 4 hours; then raised to 950°C for 2 hours and calcined for 2.5 hours; finally raised to 1300°C for 1 hour and calcined for 3 hours; the temperature was lowered in stages: lowered to 1100°C for 1 hour and maintained for 0.5 hours, then lowered to 850°C for 1 hour and maintained for 0.5 hours, and finally lowered to room temperature at a rate of 25°C / h to obtain Ta x C y Graphite substrate of the infiltration layer.

[0128] 2) Dissolve 4N grade TaC in an organic solvent to prepare a TaC-containing slurry, which includes: 40 parts of TaC powder, 35 parts of ethanol, 15 parts of tetrahydrofuran, 1 part of BYK defoamer, 5 parts of cellulose ether, 5 parts of straight-chain saturated aliphatic hydrocarbons, and 1 part of carbon powder. After mixing and stirring the above components for 2.5 hours, use a sprayer to spray the slurry onto the surface of the TaC-containing x C y The surface of the graphite substrate of the infiltration layer is placed in a heating furnace, the temperature is raised to 220°C in an air environment and dried for 8 hours, then argon is introduced into the heating furnace, sintered at 900 mbar and 500°C for 5 hours, then the pressure is raised to 1100 mbar, the temperature is raised to 1600°C, sintered for 10 hours, and finally the pressure is raised to 155 kPa, the temperature is raised to 2200°C, sintered for 14 hours, and finally cooled to room temperature and normal pressure after 15 hours to obtain crucible 3#.

[0129] Crucible 4#

[0130] The difference between this embodiment and crucible 1# is that in step 1), the graphite substrate is not subjected to gas pressurization treatment during immersion in the tantalum pentachloride n-butanol solution, but is only immersed at room temperature and pressure for 1 hour, and then dried and calcined. The other conditions are the same as those of crucible 1#, and crucible 4# is obtained.

[0131] Crucible 5#

[0132] The difference between this embodiment and crucible 1# is that in step 1), the graphite substrate after soaking and drying is calcined in a vacuum furnace by maintaining the pressure in the furnace at 900 mbar, calcining at 700°C for 7 hours, and then calcining at 1200°C for 5 hours before starting staged cooling. The other conditions are the same as those of crucible 1#, and a composite coated crucible 5# is obtained.

[0133] Crucible 6#

[0134] The difference between this embodiment and crucible 1# is that in step 2), the graphite substrate after spraying the slurry and drying is sintered in a heating furnace as follows: sintering at 1000 mbar and 1200°C for 12 hours, then the pressure is increased to 140 kPa, the temperature is increased to 2300°C, sintering for 20 hours, and finally cooled to room temperature and normal pressure after 20 hours. The remaining conditions are the same as those of crucible 1#, that is, crucible 6# is obtained.

[0135] Comparison crucible D1#

[0136] Compared with Example 1, step 1) of this comparative example is the same, and step 2) adopts the CVD method, specifically:

[0137] 2) will carry Ta x C y The graphite substrate of the permeation layer is placed in a chemical vapor deposition furnace, evacuated to below 50Pa, and then heated to 1200°C. A mixed gas consisting of ethane, TaCl5, H2 and carrier gas argon is introduced. The mixed gas enters the deposition furnace at a stable flow rate, and the furnace pressure is maintained at 5000Pa. The molar ratio of TaCl5 and ethane gas is first controlled at 1.2:1 to form a transition layer with a thickness of 50μm; then the molar ratio of TaCl5 and ethane gas is controlled to 3:1 to form a TaC coating with a thickness of 60μm, thereby obtaining the comparison crucible D1#.

[0138] Compare Crucible D2#

[0139] Compared with the comparative crucible D1#, this comparative example does not perform step 1), and only performs step 2) on the graphite substrate. Step 2) forms a transition layer and a TaC coating on the graphite substrate by a CVD method. The specific conditions of the CVD method are the same as those of the comparative crucible D1#, that is, a comparative crucible D2# is prepared.

[0140] Compare Crucible D3#

[0141] Compared with Example 1, this comparative example does not perform step 1), and only performs step 2) on the graphite substrate. The operating conditions of step 2) are the same as those of Example 1, that is, a comparative crucible D3# is prepared.

[0142] The crucibles 1#-6# and the comparative crucibles D1#-D3# prepared above were subjected to high temperature corrosion and thermochemical corrosion experiments to simulate the growth environment of the third generation semiconductor silicon carbide crystal using the PVT method. The crucibles 1#-6# and the comparative crucibles D1#-D3# were kept at 2300°C and etched in a silicon carbide atmosphere for 100 hours. The test results are shown in Table 1:

[0143] Table 1

[0144] sample Weight before experiment (g) Weight after the experiment (g) Erosion weight loss rate (%) Crucible 1# 46.7103 46.0390 1.43 Crucible 2# 47.8269 47.3314 1.04 Crucible 3# 47.1923 46.7274 0.98 Crucible 4# 46.3194 45.5326 1.70 Crucible 5# 47.5247 46.5326 2.09 Crucible 6# 47.3215 46.4137 1.91 Comparison crucible D1# 47.9024 46.3529 3.23 Compare Crucible D2# 46.7247 45.1371 3.40 Compare Crucible D3# 46.7372 45.0261 3.66

[0145] In Table 1, erosion weight loss rate = [(weight before experiment - weight after experiment) / weight before experiment] × 100%. The above high temperature erosion and thermochemical erosion experiments prove that the TaC coating of this embodiment can improve the protection performance of the graphite substrate, extend the tolerance and corrosion resistance of the TaC coating, and thus extend the service life of the crucible. Figure 3 Ta involved in crucible 1# of this application x C y EDS Mapping characterization diagram of the permeation layer, according to Figure 3 It is known that x C y The permeation layer is formed inside and on the surface of the graphite substrate and interspersed with the inside of the graphite substrate, thereby having a strong bonding force with the graphite substrate, thereby improving the durability of the crucible. x C y XRD test of the penetration layer, TaC coating and TaC can be used to obtain the Ta x C y Ta of the permeation layer x C y The grains grow anisotropically, and the TaC grains of the TaC coating grow oriented along the

[200] and

[220] directions.

[0146] The composite coating prepared in this embodiment is deposited on the surface of the graphite substrate, which can protect the graphite substrate and improve the temperature resistance and chemical corrosion resistance of the graphite substrate, thereby reducing the interference of the graphite substrate on the crystal growth environment and improving the stability of the crystal environment. The Ta can be controlled by calcining and sintering processes. x C y The oriented growth of grains in the infiltration layer and the TaC coating improves the compactness of the composite coating and can be used to prepare high-quality silicon carbide crystals.

[0147] Example 6

[0148] This embodiment relates to a method for preparing a silicon carbide single crystal, comprising the following steps:

[0149] (1) Adding silicon carbide powder into a graphite crucible;

[0150] (2) Evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300-500mbar, repeat this process 2-3 times, and finally evacuate the furnace to 10 -6 Below mbar;

[0151] (3) introducing high-purity inert gas into the furnace body, raising the pressure to 10-100 mbar within 1-3 hours, and continuously introducing high-purity inert gas and maintaining the pressure constant;

[0152] (4) Crystal growth stage: While maintaining the pressure unchanged, the temperature inside the furnace is raised to the single crystal growth temperature of 2200K-2800K within 3-5 hours, and the growth time is 30-150 hours;

[0153] (5) After the single crystal growth is completed, open the furnace body and take out the graphite crucible to obtain the silicon carbide single crystal.

[0154] Add equal amounts of silicon carbide powder to crucibles 1#-3#, crucible 5#, and comparative crucibles D1#-D3# prepared in Example 6; evacuate the furnace to 10 -6 mbar, and then introduce high-purity inert gas to 300 mbar. Repeat this process 3 times and finally evacuate the furnace to 10 -6 mbar or less; introduce high-purity inert gas into the furnace body, raise the pressure to 30 mbar within 1 hour, and continue to introduce high-purity inert gas and keep the pressure constant; crystal growth stage: while keeping the pressure constant, raise the temperature in the furnace body to 2200K within 3 hours, the growth time is 10 hours, and then raise the temperature in the furnace to 2500K within 3 hours, and the growth time is 80 hours; after the single crystal growth is completed, open the furnace body, take out the graphite crucible, and obtain silicon carbide single crystals 1#-3#, silicon carbide single crystal 5# and comparison silicon carbide single crystals D1#-D3# respectively.

[0155] The above-mentioned silicon carbide single crystals 1#-3#, silicon carbide single crystal 5# and comparative silicon carbide single crystals D1#-D3# were subjected to the same cutting, grinding, mechanical polishing and chemical polishing to obtain silicon carbide substrates 1#-3#, silicon carbide substrate 5# and comparative silicon carbide substrates D1#-D3#. In vivo stress tests were performed using the methods of Examples 1-4, and the results are shown in Tables 2 and 3.

[0156] Table 2

[0157]

[0158]

[0159] Table 3

[0160]

[0161] The stress values ​​in Table 2-3 all refer to relative stress values. In the present application, the positive and negative values ​​in the stress values ​​represent whether the substrate is subjected to tensile stress or compressive stress at the test point relative to the above-mentioned reference value. In the prior art, when evaluating and describing the final stress state of a substrate, the maximum value minus the minimum value in the above-mentioned stress values ​​is often used to obtain the difference. For example, the axial internal stress in the first square area 1# of the silicon carbide substrate is -8.8~20.4. When the axial internal stress in the annular area 1# of the silicon carbide substrate is generally expressed in this field, it can also be described as a stress value of 29.2MPa.

[0162] The surface shape of the silicon carbide substrates 1#-3# and 5# was tested, and their curvatures were all within the range of -50μm to 50μm, the local thickness deviation of the first square area was within the range of 0.1-1μm, and the local thickness deviation of the second square area was within the range of 0.1-1μm.

[0163] The data in the above Tables 2-3 are only the substrates prepared by crucibles 1#-3# prepared in Example 5 and comparative crucibles D1#-D3#. When the same crystal growth and processing methods in Example 6 are adopted and crucibles 4#-8# are used to prepare silicon carbide substrate sheets, and the parameters in Tables 2-3 are characterized by absolute stress, the ratio of the number of first square regions to the number of second square regions can be 1: (12.9-21.4); the radial internal stress of the first square region is -20 to 40 MPa, and the radial internal stress of the second square region is -10 to 20 MPa; 0.2≤S1 / S2≤1.7; 0.3≤S 3 / S4≤1.2; 1.4≤S1 / S3≤5.1; 10MPa≤△S1≤40MPa, 0MPa≤△S2≤20MPa; the axial internal stress in the first square region is -10~30MPa, and the axial internal stress in the second square region is -5~10MPa; 0.6≤S5 / S6≤1.7; 0.7≤S7 / S8≤1.2; 1.6≤S5 / S7≤4.2; 4.7MPa≤△S3≤20.4MPa; 1.2MPa≤△S4≤14.1MPa; in the first square region, the number of microtubes is less than 4, and the number of dislocations is less than 14.

[0164] The above is only the embodiment of the present application, and the protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application can have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A silicon carbide substrate with a regular crystal structure, characterized in that: The silicon carbide substrate includes a first main surface and a second main surface opposite to the first main surface; Dividing the silicon carbide substrate into a first square region containing micropipes or dislocations and having a length of 100 μm, and a second square region not containing micropipes or dislocations and having a length of 100 μm, wherein the ratio of the number of the first square regions to the number of the second square regions is 1:(12.9-21.4); The internal stress of the first square region is greater than the internal stress of the second square region. The internal stress is a stress value detected at a region vertically extending from the first main surface and / or the second main surface into the silicon carbide substrate by 30%-60% of the substrate thickness.

2. The silicon carbide substrate according to claim 1, characterized in that At any plane parallel to the first main surface and / or the second main surface, the radial internal stress of the first square area is -20 to 40 MPa, and the radial internal stress of the second square area is -10 to 20 MPa; and / or The silicon carbide substrate has a diameter of 150 mm or more.

3. The silicon carbide substrate according to claim 1, characterized in that At any plane parallel to the first main surface and / or the second main surface, S1 represents the average absolute value of the radial internal stress in all the first square regions, S2 represents the average absolute value of the radial internal stress in any of the first square regions, 0.2≤S1 / S2≤1.7; and / or At any plane parallel to the first main surface and / or the second main surface, S3 represents the average absolute value of the radial internal stress in all the second square regions, S4 represents the average absolute value of the radial internal stress in any second square region, and 0.3≤S3 / S4≤1.2; Preferably, 1.4≤S1 / S3≤5.

1.

4. The silicon carbide substrate according to claim 1, characterized in that At any plane parallel to the first major surface and / or the second major surface, S max1 S is the maximum radial internal stress in any of the first square regions, min1 Denote as the minimum value of radial internal stress in any first square region, △S1 = S max1 -S min1 , 10MPa≤△S1≤40MPa, S max2 S is the maximum radial internal stress in any second square region. min2 Denote as the minimum value of radial internal stress in any second square region, △S2 = S max2 -S min2 , 0MPa≤△S2≤20MPa.

5. The silicon carbide substrate according to claim 1, characterized in that An axial test is performed by extending perpendicularly into the silicon carbide substrate from any point of the first main surface and / or the second main surface. The axial internal stress in the first square region is -10 to 30 MPa, and the axial internal stress in the second square region is -5 to 10 MPa.

6. The silicon carbide substrate according to claim 1, characterized in that An axial test is performed by extending vertically into the silicon carbide substrate from any point of the first main surface and / or the second main surface, S5 represents the average absolute value of the axial internal stress in all the first square regions, S6 represents the average absolute value of the axial internal stress in any of the first square regions, 0.6≤S5 / S6≤1.7; and / or An axial test is performed by extending vertically into the silicon carbide substrate from any point of the first main surface and / or the second main surface, S7 represents the average absolute value of the axial internal stress in all the second square regions, S8 represents the average absolute value of the axial internal stress in any second square region, and 0.7≤S7 / S8≤1.2; Preferably, 1.6≤S5 / S7≤4.

2.

7. The silicon carbide substrate according to claim 1, characterized in that: An axial test is performed by extending vertically into the silicon carbide substrate from any point of the first main surface and / or the second main surface, S max3 S is the maximum axial internal stress in any of the first square regions, min3 Denote as the minimum axial internal stress in any of the first square regions, △S3 = S max3 -S min3 ,4.7MPa≤△S3≤20.4MPa,S max4 S is the maximum axial internal stress in any second square region. min4 Denote as the minimum axial internal stress in any of the first square regions, △S4 = S max4 -S min4 ,1.2MPa≤△S4≤14.1MPa.

8. The silicon carbide substrate according to claim 7, characterized in that: 4.7MPa≤△S3≤13.5MPa, 1.2MPa≤△S4≤8.4MPa.

9. The silicon carbide substrate according to claim 1, characterized in that: In the first square region, the number of microtubes is less than 4, preferably 0; or In the first square region, the number of dislocations is less than 14, preferably 0.

10. The silicon carbide substrate according to claim 1, characterized in that The ratio of the number of the first square regions to the number of the second square regions is 1:(19.7-21.4).